Sacred texts and paradigmatic revolutions : the hermeneutical worlds of the Qumran sectarian manuscripts and the letter to the Romans /: the hermeneutical worlds of the Qumran sectarian manuscripts and the letter to the Romans. (2013) - Unknown
No abstract available